GEOMETRIA E CARATTERI STRATIGRAFICI DELLA SEQUENZA CENOMANIANA NEL BACINO LOMBARDO (ALPI MERIDIONALI) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
The Cenomanian Sequence in the area between the lakes of Lecco and Iseo (Lombardy Basin, Southern Alps) represents a depositional unit bounded by two main unconformities and relative conformities. The unconformities progressively develop from SW to NE, with hiatuses spanning in age the Early Cenomanian and the Late Cenomanian-Turonian respectively.A complete section of the Cenomanian Sequence consists of Early Cenomanian red marls with pelagic turbidites and pebbly mudstones (Marne rosse) followed by two calcareous chaotic layers enclosing a succession of thin bedded, fine grained siliciclastic turbidites (Torbiditi Sottili), of Middle to Late Cenomanian age.The association of chaotic layers with the enclosed wedge shaped body of turbidites and the development of unconformities towards the north, point out that the Cenomanian basin developed in a mobile area where deposition was controlled by sinsedimentary tectonics. Moreover, the Cenomanian basin is, so far, the youngest Cretaceous basin clearly documented in the Southern Alps, oriented east-west, therefore crosswise to the structures related to the Jurassic rifting. Stratigraphic data strongly suggest that the tectonic evolution of the northern margin of the Cenomanian Lombardy Basin was generated by compression with the development of antiform structures.The sandstone unit pinches out towards the north and east, and thins more gradually towards the south. It represents a wedge shaped body, which parallels E-W paleocurrent trends and onlaps onto the northern margin of the Cenomanian basin. The two chaotic layers are basinally extended and show facies changes and thinning from north to south. They derived from sliding and slumping of the northern slope of the basin.
Keywords: Southern Alps; Lombardy Basin; Cenomanian; Depositional Sequences.